DESIGN AND DEVELOPMENT OF FLIGHT CONTROLLER FOR QUADCOPTER DRONE CONTROL - Muhamad, Aidil; Panjaitan, Seno Darmawan; Yacoub, Redi Ratiandi (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2024)
UAV (Unmanned Aerial Vehicle), also commonly called drone, is a flying robot technology that can be controlled remotely and can also fly autonomously based on the mission given by the operator. Drones are usually used for various purposes such as package delivery, watering plants, land mapping, natural disaster monitoring, photography, videography and others. Drones have many types, one of which is a drone with four motors as the main drive, commonly called a quadcopter drone. Quadcopter drones have evolved a lot based on current needs. Although quadcopter drones have many uses, the development of quadcopter drone research in Indonesia is quite slow, one of the quadcopter drone components whose development is quite slow is the flight controller. Flight controller (FC) is a main controller brain in drones that has complex functions in quadcopter drone control. The function of the FC is to regulate motor speed, stabilize and maintain altitude. In this research, FC is designed to control the stability of quadcopter drones while flying. This FC was developed by applying LoRa technology as an internal receiver. LoRa technology is used to receive control data from the remote control (RC) and simultaneously send sensor data. The purpose of this research is to design FC to improve local products in the field of technology and participate in the development of flying robot technology, especially on quadcopter drones and to determine the performance of LoRa technology after being integrated as an internal transceiver in FC for remote control of quadcopter drones.